Caracterização de interações entre matéria orgânica natural e íons metálicos por ultrafiltração em fluxo tangencial com múltiplos estágios. - Santos, Adilson Costa (2009)
In this work the interactions between metallic the natural organic matter and ions by means of the technique of the ultrafiltration in tangential flow with multiple stagess of training had been characterized. For such, water samples of the Grotto of the Mountain range of the National Park Mountain range of Itabaiana (SE) had been collected. Amongst the main determined parameters, they are distinguished pH, the DOC, the absorbances in 254 and 436 nm, the complexation capacity in relation to the Cu (II) ion and the concentrations of thirty and three elements. The sample was submitted the ultrafiltration in tangential flow, with five stages of training, getting itself six fractions with thus described molecular sizes in kDa: F1 : > 100; F2 : 100-50; F3 : 50-30; F4 : 30-10; F5 : 10-5 and F6 : < 5. The concentrations of nine metals (Al, Ba, Cr, Cu, Fe, Mn, Ni, Pb and Sr.), the DOC, the absorbances in UV-Vis and the molecular fluorescence had been determined in the six fractions. The results had shown that the fractions F2 and F5 had been richest in humics substances. They had added aliquot of metallic solutions of nine ions (Al3+, Ba2+, Cr3+, Cu2+, Fe3+, Mn2+, Ni2+, Pb2+ and Sr2+) the 1 L of sample, that was kept under magnetic agitation during 30 days. In the times of 1, 7, 15 and 30 days had been effected new fractionaments for inquiry of the DOC and metallic texts of ions in the fractions. The distribution of added metallic DOC and ions varied through the diverse times of complexation. The stability constants of the complexes formed between the natural organic matter and metals aluminum, cooper and iron also had been determined by the method of the ultrafiltration, getting itself log K (Al) = 7,1, log K (Cu) = 6,6 and log K (Fe) = 7,6. The characterization of the natural organic matter allowed to evaluate the high one to be able buffering of the same one in relation to metallic ions, as well as proving the preservation of the source in study